Abrasion Resistance and Water Absorption Characteristics of Ti-HAp Hybrid Reinforced Polyetheretherketone Biocomposites - Itua, Agbeboh Newton; Oluwole, Oladele Isiaka; Ojo, Daramola Oluyemi; Hope, Adegun Miracle (Applied Science and Engineering Progress, 2023)
The influence of abrasion on biomedical implant in human body is a constant cause of pain, discomfort and sometimes a repeat of surgery as a result of the complications from the effects of wear on the implants and the negative consequences of the resultant abrasive particles on the surrounding tissue and bodily environment. To alleviate this, a titanium-hydroxyapatite hybrid reinforced polyetheretherketone (PEEK) biocomposite material was developed, characterized and tested. X-Ray Diffraction characterization revealed that the calcined eggshell was composed mainly of lime and portlandite. The calcined eggshell was then used in the synthesis of hydroxyapatite powder (HAp) with characteristic bands confirmed by FTIR spectroscopic analysis. Biocomposites were developed from the blend of titanium and hydroxyapatite powders in varying proportions as reinforcements in PEEK matrix. The developed composites and control sample were subjected to abrasion and water absorption tests from where it was revealed that biocomposite sample reinforced with 10 wt.% orthophosphoric acid synthesized eggshell possess optimum abrasion resistance with a wear index of 0.20 mg/cycle with an acceptable level of water absorption next to the unreinforced polyetheretherketone over a period of 35 days.